2008
DOI: 10.1007/s11661-007-9429-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of Sn-Co-Ni System and Interfacial Reactions in Sn/(Co, Ni) Couples

Abstract: Sn-Co-Ni alloys of 25 different compositions have been prepared and equilibrated at 250°C. A new ternary (Ni, Co)Sn 4 phase is found, and all the binary compounds have very significant mutual solubilities between Co and Ni. According to the ternary equilibrium phase data and the constituent binary phase diagrams, the 250°C isothermal section of the Sn-Co-Ni system is proposed. In the Sn-CoSn-Ni 3 Sn 4 corner, there are nine two-phase regions and five tie-triangles. Interfacial reactions between molten Sn and N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 17 publications
5
27
0
Order By: Relevance
“…On the other hand, Chao et al reported interfacial reactions in Sn/(Co,Ni) couples at 250°C. 13 They reported that only one layer of Ni 3 Sn 4 IMCs is formed in the reactions of Sn/Ni-1at.%Co couples at 250°C, while two layers of (Ni,Co)Sn 4 and Ni 3 Sn 4 IMCs formed in the reactions of Sn/Ni-3at.%Co, Sn/Ni-5at.%Co, and Sn/Ni-20at.%Co couples. 13 In addition, the morphology of (Ni,Co)Sn 4 IMCs are plate-like.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, Chao et al reported interfacial reactions in Sn/(Co,Ni) couples at 250°C. 13 They reported that only one layer of Ni 3 Sn 4 IMCs is formed in the reactions of Sn/Ni-1at.%Co couples at 250°C, while two layers of (Ni,Co)Sn 4 and Ni 3 Sn 4 IMCs formed in the reactions of Sn/Ni-3at.%Co, Sn/Ni-5at.%Co, and Sn/Ni-20at.%Co couples. 13 In addition, the morphology of (Ni,Co)Sn 4 IMCs are plate-like.…”
Section: Resultsmentioning
confidence: 99%
“…13 They reported that only one layer of Ni 3 Sn 4 IMCs is formed in the reactions of Sn/Ni-1at.%Co couples at 250°C, while two layers of (Ni,Co)Sn 4 and Ni 3 Sn 4 IMCs formed in the reactions of Sn/Ni-3at.%Co, Sn/Ni-5at.%Co, and Sn/Ni-20at.%Co couples. 13 In addition, the morphology of (Ni,Co)Sn 4 IMCs are plate-like. 13 In this present work, the ternary compound Ni 22 Co 6 Sn 72 is similar to the (Ni,Co)Sn 4 IMC Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…5,7 Although it is obvious that knowledge regarding Co solubility in molten Sn at the Sn-rich corner is very important for better understanding of the effects of Co addition, there is only limited and even inconsistent information on Sn-Co phase equilibria in the literature. 6,[16][17][18] A second aim of this study is thus to determine Co solubility in molten Sn in the Sn-Co system at the Sn-rich corner.…”
Section: Introductionmentioning
confidence: 99%